Our Schubert [ his enduring legacy - Schroeder, David P. , 1946- (Scarecrow Press, 2009)
This volume analyzes some of the uses of Austrian composer Franz Schubert's (b. 1797) music, examining the man, his compositions, and the ways audiences and artists, both his contemporaries and their descendants, connect with him. Schubert is admired as one of the leading exponents of the early Romantic era in music and he remains one of the most frequently performed composers